The Antecedent Factors of Knowledge Sharing Amongst International School’s Teachers - Fajardini, Zahra; Herawati, Tuti; Suparman, Asep; Anggiani, Sarfilianty (Syntax Literate, 2025)
This study aims to find out and test the influence of Organisational Social Capita, Attitude and Cultural Intelligence on Knowledge Sharing (KS) on educators in international schools or what is now called SPK (Cooperative Education Unit) schools. Design/Methodology of the research - Data was collected from 126 foreign and local teachers in various cities, namely Jakarta, South Tangerang, Bogor, and Pekanbaru using the online questionnaire survey method and using the Structural Equation Model method with Smart PLS to analyze the relationship between 3 independent variables: Organisational Social Culture, Attitude and Cultural Intelligence to the dependent variable namely Knowledge Sharing (KS) and test a series of hypotheses Findings: There is a significant relationship between Attitude and Cultural Intelligence towards Knowledge Sharing, while Organisational Social Capital does not have a significant influence on Knowledge Sharing. Limitations/Implications of the Research: This study assists the management of International schools (SPK (Cooperative Education Units)) in establishing human resource policies such as recruitment, placement and making training designs that can provide social skills stimulus so that knowledge sharing can occur optimally in a multicultural setting in SPK schools (International schools). For the next study, it can involve a larger number of respondents and add indicators of social interaction and team innovation that are not included in the variables studied in this study. Originality/value: This study is the first empirically to use Organisational Social Capital, Attitude and Cultural Intelligence in analyzing the relationship between knowledge sharing in international schools (SPK Schools). Further studies are needed to contribute more to the governance of educational services, especially in SPK schools in Indonesia.